Fine-root production in boreal peatland forests: Effects of stand and environmental factors - He, Wei; Mäkiranta, Päivi; Straková, Petra; Ojanen, Paavo; Penttilä, Timo; Bhuiyan, Rabbil; Minkkinen, Kari; Laiho, Raija (Elsevier, 2023)
Fine roots are an important component of ecosystem carbon (C) cycling in boreal forests and peatlands. We aimed to estimate fine-root production (FRP) for a range of peatland forests, examine the patterns in, and develop models for estimating, the relationships between FRP and tree stand characteristics as well as environmental conditions. Fine-root production of 28 drained boreal peatland forest sites in Finland, representing different site types and soil water-table conditions, was measured using the ingrowth-core method. Total FRP and FRP of conifers decreased from south to north but long-term mean annual temperature sum and precipitation alone did not significantly explain this trend. Tree stand basal area predicted FRP better than any other stand variable alone, explaining 16 % of the variation in stand-level total FRP. Basal areas of pine and spruce correlated positively with the FRP of conifers. Total FRP varied considerably among the site types and, with the exception of the most fertile site type, decreased with decreasing fertility. A model that included stand basal area and site type accounted for 47% of the variation in stand-level total FRP. Total FRP was generally higher with a deeper water-table level (WT). Together, WT and basal area explained 25 % of the variation in stand-level total FRP. Most FRP occurred in the top 20-cm layer comprising 76–95% of total FRP. The most fertile site type showed lower FRP in deeper layers than the other site types. These results can be used for estimation of FRP with forest inventory data.
Keywords: Ingrowth core; Fourier transform infrared (FTIR) spectroscopy; suot; suometsät; juuret; Fine roots; Forestry-drained peatland